TEACHER RETENTION POLICY IN THE UK: INNOVATIVE APPROACHES AND PRACTICAL SOLUTIONS - Vyhovska, Olha (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2024)
The article studies the problem of teacher retention policy in the profession on the example of the United Kingdom. Innovative approaches to motivating teachers to stay in the profession are analyzed and practical solutions that can be adapted in Ukraine are proposed. It is concluded that the lack of homogeneity in the teaching profession is an important aspect of the problem of this study, which aims to assess the attractive aspects of the teaching profession and develop a system of measures that will contribute to the attractiveness of this profession in the future. It has been found that there is a steady upward trend in the number of teachers leaving the profession every year. Educational researchers and government officials in many countries are working to overcome this crisis. It has been found that the lack of qualified teachers in certain areas, subjects, or to work with children with special needs can be an important factor in the development and implementation of the necessary measures to encourage future entrants to teaching, which requires targeted action at the level of reforming public education policy. An analysis of the UK’s teacher retention policy demonstrates the importance of a comprehensive approach to addressing the teacher shortage. The UK experience shows the need to reduce the professional workload of teachers; support for the well-being and working conditions; reform of the remuneration system; investment in professional development; raising the social prestige of the teaching profession; implementation of targeted policies, etc. It is emphasized that the governments of the leading European countries understand the importance of this problem and emphasizes that modern teachers should not only transmit knowledge but also act as facilitators, as they teach students with different socio-economic backgrounds, interact with families of different cultural backgrounds, create an appropriate learning environment for children with special educational needs, etc.